High photosensitized singlet oxygen generating zinc(II) and indium(III) acetate phthalocyanines containing 6,8-di-tert-butyl-3-(p-oxyphenyl)coumarin groups - Soyer Can, Okşan; Kaya, Esra Nur; Bulut, Mustafa; Durmuş,Mahmut (My University, 2016)
The novel 6,8-di-tert-butyl-3-(p-hydroxyphenyl)coumarin (1) and its phthalonitrile derivatives named 4-[6,8-di-tert-butyl-3-(p-oxyphenyl)coumarin]phthalonitrile (2), 3-[6,8-di-tert-butyl-3-(p-oxyphenyl)coumarin]phthalonitrile (3), 4,5-bis[6,8-di-tert-butyl-3-(p-oxyphenyl)coumarin]phthalonitrile (4) and 4-chloro-5-[6,8-di-tert-butyl-3-(p-oxyphenyl)coumarin]phthalonitrile (5) were synthesized. These phthalonitrile derivatives were also converted to the corresponding zinc(II) (2a-5a) and indium(III)(OAc) (2b-5b) phthalocyanines bearing four or eight 6,8-di-tert-butyl-3-(p-oxyphenyl)coumarin groups. All novel compounds synthesized in this study were fully characterized by elemental analysis and general spectroscopic techniques such as FT-IR, UV-vis, 1H NMR and mass. Additionally; spectral, photophysical (fluorescence quantum yields and lifetimes) and photochemical (singlet oxygen generation and photodegradation under light irradiation) properties of 6,8-di-tert-butyl-3-(p-oxyphenyl)coumarin substituted zinc(II) and indium(III)(OAc) phthalocyanines were investigated in N,N-dimethylformamide (DMF) solutions. The effects of number or position of the substituents and the type of central metal atoms on these properties were also determined. All studied phthalocyanines showed excellent solubility in general organic solvents. They also produced good singlet-oxygen and showed appropriate photodegradation by light irradiation. © 2015 Elsevier B.V.
Keywords: Coumarin; Fluorescence; Photodegradation; Phthalocyanine; Singlet oxygen